Lifecycle Cost and Carbon Emissions Evaluation of Electric and Gasoline Vehicles in Kathmandu: A Case Study of the TATA Nexon - Pradhan, Rush; Lamichhane, Binaya Kumar; Pandey, Shristi; Chaulagain, Pitambar (International Journal on Engineering Technology and Infrastructure Development, 2025)
The rising global concern about greenhouse gas emissions and the economic burden of fossil fuels underscores the need for sustainable transportation solutions, particularly in densely populated cities like Kathmandu. The main aim of the study is to evaluate the cost efficiency and environmental impact of electric vehicles (EVs) compared to internal combustion engine vehicles (ICEVs) in Kathmandu Valley, focusing on and using a case of the TATA Nexon XZ+ models in both petrol and electric variants. The analysis involved calculating the Total Cost of Ownership per kilometer (TCO/km) and CO2 emissions, using data from the Nepal Oil Corporation for fuel prices and the Nepal Electricity Authority for electricity tariffs. A detailed economic cost model was used, which included the initial purchase costs, ongoing operational expenses, and maintenance fees and all these costs were adjusted to reflect their value in today's terms by discounting them to present values. A sensitivity analysis was conducted to investigate how variations in annual kilometers traveled and initial purchase prices impact the total cost of ownership per kilometer (TCO/km). The findings reveal the EV variant offers a lower TCO/km, achieving savings of Rs. 22.6 per km, primarily due to lower fuel and maintenance costs. Environmentally, EVs offer substantial benefits by eliminating tailpipe emissions, a major contributor to CO2 emissions from petrol vehicles.